Postoperative cognitive dysfunction: spotlight on light, circadian rhythms, and sleep - Campbell, Ellie; Figueiro, Mariana G. (Frontiers in Neuroscience, 2024)
Postoperative cognitive dysfunction (POCD) is a neurological disorder characterized by the emergence of cognitive impairment after surgery. A growing body of literature suggests that the onset of POCD is closely tied to circadian rhythm disruption (CRD). Circadian rhythms are patterns of behavioral and physiological change that repeat themselves at approximately, but not exactly, every 24 h. They are entrained to the 24 h day by the daily light–dark cycle. Postoperative CRD affects cognitive function likely by disrupting sleep architecture, which in turn provokes a host of pathological processes including neuroinflammation, blood–brain barrier disturbances, and glymphatic pathway dysfunction. Therefore, to address the pathogenesis of POCD it is first necessary to correct the dysregulated circadian rhythms that often occur in surgical patients. This narrative review summarizes the evidence for CRD as a key contributor to POCD and concludes with a brief discussion of how circadian-effective hospital lighting can be employed to re-entrain stable and robust circadian rhythms in surgical patients.